Avaliação de fatores operacionais em processo de peneiramento vibratório aplicado à separação sólido-líquido com o auxílio de técnicas de análise de imagem - Barbosa, Vinícius Pimenta (2018)
During the drilling of oil wells, the drilling fluid is injected into the drilling column, which has several functions such as: driving the solids from the rock cutting to the surface, lubricating the drilling column, cooling the drill bit, stabilizing the well, among others. To recondition this fluid, the solid control unit is used, which aims to remove the solids produced by the rock drilling and to recondition the fluid so that it returns to the drilling process. The first equipment of the solid control unit is the vibrating screen. The objective of this study was to evaluate the vibration screening operation applied to the solid-liquid separation against the effect of the independent variables: g-force, volumetric concentration of solids in the feed, feed rate and slope of the sieving screen. A central composite design for the experiments with a reply in the center point was made, totalizing of 26 experiments. The dependent variables were: residual moisture content of retained solids, pool area, transport velocity of solids retained in the beach region and percentage of screen area occupied by solids retained in the beach region. For the liquid part of the suspension, water with 0.1% by mass of xanthan gum was used, while for the solid part, standardized sand with a mean Sauter diameter of 373 μm. The screen used in the sieve was 175 mesh. By the analysis of the results, it was possible to verify that the lowest value of pool area was 906,695 cm², resulting from the combination of the highest levels of g-force (5), volumetric solids concentration in the feed (5%), and screen inclination (3.5º), with the lowest level of feed rate (19 kg / min). For the residual moisture content of the retained solids, a strong influence of the force-g variables and volumetric concentration of solids in the feed was observed, with the highest residual moisture value of 22.862%, for the combination of higher g-force level (5) and lower volumetric solids concentration in the feed (3%). The lowest residual moisture content of the retained solids was 19.211%, for the lowest level of g-force (2.5) combined with the highest solids concentration (5%). The highest transport velocity of the retained solids was 17.00 cm/s, for the combination of the highest levels of g-force (5), solids volume concentration (5%) and slope (2.5º) with the lowest level of feed rate (25 kg / min). It was also observed that higher transport velocities have a great influence on the decrease of the percentage of screen area occupied in the beach region by the retained wet solids. The conclusion was that the increase in g-force and inclination variables increase the operational capacity of the screen, because it reduces the pool area beyond the screen area occupied by the retained solids. Proper maintenance of these variables allows to correct deviations caused by fluctuations in the feed rate and volumetric solids concentration.